Toxicity of Antifungal Drugs Itraconazole and Fluconazole in Rats - Abdul Rahman, Nor Shahida (2004)
Itraconazole and Fluconazole are the newer antifungal drugs that have been used for several years. Both these drugs have a broad-spectrum antifungal activity and currently are used to treat infections caused by Candida albicans, Aspergillus spp., Paracoccidioides brasiliensis, Sporothrix schenckii, Histoplasma capsulatum, Ciyptococcus neoformans and many others. The objective of this study is to investigate the in vitro and in vivo cytotoxicity of these two antifungal drugs. The in vitro and in vivo cytotoxicity of fluconazole and itraconazole were studied in thirty eight male Sprague Dawley rats. Freshly isolated rat hepatocytes were obtained for the in vitro treatment of fluconazole and itraconazole using a liver perfusion technique. The cell viability test was done by trypan blue exclusion. As a result, both fluconazole and itraconazole cause a reduction in cell viability of hepatocytes. However, itraconazole exerted its cytotoxicity more than fluconazole in both time- and dosedependent manner. Meanwhile, cytotoxicity of itraconazole was reduced significantly by Phenobarbital pretreatment. Phenobarbital did not have any effect on the .-. i l l cytotoxicity induced by fluconazole. In vivo studies revealed that rat's liver and kidney treated with repeated-doses of itraconazole showed a significantly higher in total protein in liver and kidney and significant increase in serum ALP and ALT activity. This is in agreement with histological findings that the rat treated with repeateddoses of itraconazole showed severe histological features compared to fluconazole. Morphological changes such as inflammation and fibrosis of liver were frequently seen in repeated-doses of itraconazole. This present study suggests that Phenobarbital plays a role in the cytoprotection of hepatocytes to itraconazole-induced but not fluconazole-induced cytotoxicity in vitro.